KOMPARASI BIAYA PRODUKSI AYAM BROILER INDONESIA DAN BRASIL UNTUK ANTISIPASI IMPOR DAGING AYAM - Nyak Ilham; Sudi Mardianto; nFN Sumedi (Analisis Kebijakan Pertanian, 2021)
Brazil is a major exporter of chicken meat in the world and is currently is trying to enter the Indonesian market. If chicken meat from Brazil succeeds in entering the Indonesian market, the national chicken industry will be affected. This study aimed to compare the competitiveness of the national and Brazilian poultry production costs. The information used was obtained from various sources, such as national dan international scientific journals reports, and media, and data from Statistics Indonesia. The information were analyzed descriptively. In 2017-2019 broiler production costs in Brazil were from IDR 9,530 to IDR 12,060, while in Indonesia were from IDR 15,465 to IDR 17,750 per kg live weight. The low production cost of Brazilian poultry was supported by this country being the main corn producer and vegetable oil in the world, a relatively large business scale, and supported by the government. In order for Indonesia to be able to compete, the national  poultry industry needs to explore the potential of local feed materials other than corn, such as cassava, palm kernel meal, crude palm oil, rice bran, as well as Black Soldier Flies as protein source. The government role needs to be focused on monitoring the quality and quantity of DOC and disease control through vaccination and application of biosecurity to reduce mortality and increase productivity. In addition, the use of Closed House System technology in cooperation with the partner breeders is expected to increase domestic poultry business scale and efficiency.AbstrakBrasil merupakan eksportir utama daging ayam di dunia dan saat ini sedang berusaha memasuki pasar Indonesia. Apabila daging ayam dari brazil berhasil masuk ke pasar Indonesia, maka industri ayam nasional akan terpengaruh. Tulisan ini bertujuan untuk membandingkan daya saing produk unggas nasional dan Brasil dari sisi biaya produksi.  Informasi yang digunakan diperoleh dari berbagai sumber, seperti jurnal ilmiah, laporan, dan media lain lingkup nasional dan intenasional, serta data dari BPS. Informasi yang diperoleh dianalisis secara deskriptif. Pada ytahun 2019-2019 biaya produksi ayam broiler di Brasil berkisar antara Rp9.530 – Rp12.060, sedangkan di Indonesia berkisar Rp15.465 - Rp17.750 per kg berat hidup. Rendahnya biaya produksi ini disebabkan Brasil merupakan produsen utama jagung dan minyak nabati dunia, skala usaha relatif besar, dan didukung oleh kebijakan pemerintah. Agar Indonesia dapat bersaing, hal utama yang perlu dilakukan adalah menggali potensi bahan baku pakan lokal selain jagung, seperti ketela pohon, bungkil inti sawit, crude palm oil, dan dedak padi, serta Black Soldier Flies. Peran pemerintah perlu ditingkatkan dalam pengawasan kualitas dan kuantitas DOC dan pakan yang beredar, pengendalian penyakit melalui vaksinasi dan penerapan biosecurity untuk menekan angka mortalitas dan meningkatkan produktivitas. Selain itu, penggunaan teknologi kandang tertutup pada peternak mitra dapat meningkatkan skala dan efisiensi usaha.